A DFT Study on Transition States of Inhibition of Oxidation by α‐Tocopherol. Issue 29 (4th August 2020) - Yamabe, Shinichi; Tsuchida, Noriko; Yamazaki, Shoko
Abstract: DFT calculations were performed for reactions of α‐tocopherol (α‐TocH) with peroxy radicals LOO . s, tert ‐Bu‐O2 ., Me‐HC(‐O2 . )‐CH=CH‐CH=CHMe, Cl3 C‐O2 . and F3 CCH(Cl)‐O2 ., so as to examine the anti‐oxidant activity of vitamin E. 2, 2, 5, 7, 8‐Pentamethyl‐6‐chromanol (PMCH) was also used as a parent substrate to investigate the effect of the alkyl side chain, phytyl (CH2 CH2 CH2 CH(CH3 ))3 CH3 group, of α‐TocH on the reactivity. The effect of ethanol which is a standard solvent for vitamin E on its reactivity was carefully examined in a system composed of 2, 6‐di‐ tert ‐butyl‐4‐(4′‐methoxyphenyl)‐phenoxyl radical and α‐TocH. All the reaction paths were found to be not with hydrogen‐atom migration but with proton migration. Two types of transition states of LOO . + α‐TocH → LOOH + α‐Toc . were found. One is the concerted proton‐electron transfer for neutral peroxy radicals. The other is the modified single‐electron transfer followed by the Grotthuss‐type proton transfer with intervention of ethanol molecules for electron‐withdrawing peroxy radicals. Abstract : DFT calculations were performed for reactions of α‐tocopherol (α‐TocH) with various peroxy radicals so as to examine the anti‐oxidant activity of vitamin E. Two mechanisms (concerted proton‐electron transfer (CPET) and single‐electron transfer followed by proton transfer (SET‐PT)) were found to control reaction paths.